Social responsibility of business and business social analysis - Tataryntseva (Kurbatova), Yu. L.; Yurieva, Iryna (Національний технічний університет "Харківський політехнічний інститут", 2024)
The course deals with the main issues related to the theory and practice of social responsibility of business in terms of applying the principles of social management at different levels. The discipline is one of the main normative disciplines in the block of humanitarian and socio-economic training taught to masters in the fifth year. It is designed to develop students' theoretical knowledge of social responsibility of business, social systems, organisational levels of social responsibility, types, structures and patterns of corporate social responsibility. It can also be useful for postgraduate students and students of financial and economic, management specialities.
Keywords: textbook; business; social responsibility of business; business social analysis; principles of social management; social systems